2010
DOI: 10.1088/1475-7516/2010/03/010
|View full text |Cite
|
Sign up to set email alerts
|

A note on second-order perturbations of non-canonical scalar fields

Abstract: We study second-order perturbations for a general non-canonical scalar field, minimally coupled to gravity, on the unperturbed FRW background, where metric fluctuations are neglected a priori . By employing different approaches to cosmological perturbation theory, we show that, even in this simplified set-up, the second-order perturbations to the the stress tensor, the energy density and the pressure display potential instabilities, which are not present at linear order. The conditions on the Lagrangian under … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[7]; in this context, also see Ref. [17]). So, during inflation, in addition to w < −(1/3), we require that c 2 S > 0.…”
Section: An Interesting Implication For Inflationmentioning
confidence: 88%
“…[7]; in this context, also see Ref. [17]). So, during inflation, in addition to w < −(1/3), we require that c 2 S > 0.…”
Section: An Interesting Implication For Inflationmentioning
confidence: 88%
“…A well-known example of a non-valid case is the class B family of Bianchi models [19]. The class of spatially homogeneous Bianchi cosmologies including, the FLRW space-time and Bianchi IX, are valid cases [19][20][21]. Also, in the case of FLRW space-time, this is valid up to second-order in perturbations [21].…”
Section: Tionmentioning
confidence: 99%
“…In ref. [54], it was shown that when the metric perturbations are frozen then the two approaches do not, in general, lead to the same expressions. In this work we address the issue by including the metric perturbations in the theory.…”
Section: Jcap08(2015)050mentioning
confidence: 99%
“…To confirm or infirm the result of ref. [54], that the two approaches lead to different results we focus on non-canonical scalar field, i.e., setting G(X, ϕ) = 0.…”
Section: Jcap08(2015)050mentioning
confidence: 99%
See 1 more Smart Citation